2017
DOI: 10.1186/s12911-017-0559-5
|View full text |Cite
|
Sign up to set email alerts
|

Automatic schizophrenic discrimination on fNIRS by using complex brain network analysis and SVM

Abstract: BackgroundSchizophrenia is a kind of serious mental illness. Due to the lack of an objective physiological data supporting and a unified data analysis method, doctors can only rely on the subjective experience of the data to distinguish normal people and patients, which easily lead to misdiagnosis. In recent years, functional Near-Infrared Spectroscopy (fNIRS) has been widely used in clinical diagnosis, it can get the hemoglobin concentration through the variation of optical intensity.MethodsFirstly, the prefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…The disadvantage of PCA was that the principle components could not be attributed to the data from the specific channel, thus concealing the regional neurophysiological changes. Using the FCS from three channels, the achieved performance was comparable to the current results: accuracy at 70–86%, sensitivity at 70–84%, and specificity at 65–93% (Arbabshirani et al, 2013 ; Chuang et al, 2014 ; Li et al, 2015 ; Pina-Camacho et al, 2015 ; Song et al, 2017 ). The method was not calculated from the time-domain values on single or multiple channels.…”
Section: Discussionsupporting
confidence: 82%
“…The disadvantage of PCA was that the principle components could not be attributed to the data from the specific channel, thus concealing the regional neurophysiological changes. Using the FCS from three channels, the achieved performance was comparable to the current results: accuracy at 70–86%, sensitivity at 70–84%, and specificity at 65–93% (Arbabshirani et al, 2013 ; Chuang et al, 2014 ; Li et al, 2015 ; Pina-Camacho et al, 2015 ; Song et al, 2017 ). The method was not calculated from the time-domain values on single or multiple channels.…”
Section: Discussionsupporting
confidence: 82%
“…Both linear and nonlinear data can be processed by the SVM method with superior generalization performance [15]. It has been successfully applied to explore morphological neuroimaging biomarkers for the classification and diagnosis of different subsets of neurological diseases, including Alzheimer's disease (AD) and schizophrenia [16,17]. Based on published morphological studies of patients with tinnitus, the SVM method could also effectively extract neuroimaging biomarkers for tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compared to fMRI, fNIRS has several advantages such as ease of use, mobility, being inexpensive and there are several studies that utilizes fNIRS data to classify several psychiatric disorders such as depression (Husain et al, 2020; Takizawa et al, 2014; Zhu et al, 2020), schizophrenia (Azechi et al, 2010; Chuang et al, 2014; Dadgostar et al, 2018; Einalou et al, 2016; Hahn et al, 2013; Ji et al, 2020; Koike et al, 2017; Z. Li et al, 2015; Song et al, 2017) using machine learning techniques. High classification accuracies revealed that fNIRS might be a promising tool to identify the levels of flourishing and also closely related to other psychiatric disorders (Baskak, 2018; Ehlis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%